A Survey of Practitioner’s Knowledge of Psychiatric Medication Costs - Rajpoot, Deepak; Poje, Albert B; Carver, Larry; Rajpoot, Jyoti; Rajpoot, Ravi; Panwar, Vikram; Foster, Amanda; Mayorga, Angela; Shenkman, Lisa (Kansas Journal of Medicine, 2013)
Introduction. Escalating medical costs continue to be an issue facing contemporary medicine. One factor contributing to this escalation may be physicians’ knowledge of medication costs. As physicians increasingly face opportunities to treat a variety of symptoms and conditions in a single patient, including co-morbid psychiatric disorders or complications, accurate knowledge of medication costs becomes increasingly important. Methods. Resident and attending physicians (N = 16) across the disciplines of internal medicine, psychiatry, and combined internal medicine/psychiatry from a large, mid-western medical school were surveyed on the costs of several medications that are used to manage physical and psychiatric symptoms. Results. Differences were found in the perceived estimated cost of medications among practitioners particularly with specialty internal medicine training as compared to those with additional psychiatric training/experience. Trends also were noted across practitioners with psychiatric and internal medicine/psychiatry training. Conclusions. The breadth of training and experience can affect accuracy in estimating anticipated costs of medication regimens.